Effect of isometric handgrip exercise on cognitive function: Current evidence, methodology, and safety considerations - Zhu, Yuxin; He, Shan; Herold, Fabian; Sun, Fenghua; Li, Chunxiao; Tao, Sisi; Gao, Tian-Yu (Frontiers in Physiology, 2022)
Cognitive function is essential for most behaviors of daily living and is a critical component in assessing the quality of life. Mounting prospective evidence supports the use of isometric handgrip exercises (IHE) as a small muscle mass practice to promote health-related outcomes in clinical and healthy populations. The aim of the present review was to systematically investigate whether IHE is effective in improving the cognitive function of adults (aged ≥18 years). Studies were identified by searching five databases (CINAHL, MEDLINE, SPORTDiscus, PsychINFO, and Web of Science). Eight out of 767 studies met the inclusion criteria, including three types of studies: (1) acute effect for IHE with various intensity protocols (n = 4); (2) acute effect for IHE with one set exhaustion protocol (n = 2); and (3) chronic effect of IHE on cognitive function (n = 2). To assess the methodological quality of studies, the PEDro scale was used (mean score = 6.75). The evidence on whether IHE exerts acute positive effects on cognitive performance is currently rather inconclusive. However, a trend was discernible that implementing IHE can generate a beneficial chronic effect on cognitive function, although the results should be interpreted with caution. The clinical relevance of IHE as a time-efficient type of physical exercise to improve cognitive function warrants further investigation. Methodology and safety considerations were discussed.